Media image of professional workers of the centers for social work in the Republic of Serbia and the quality of reporting on their work - Skorupan, Tamara (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Negative media coverage of social work and practitioners creates a distorted public image of this profession, which arouses repulsion and mistrust among potential users, and dissatisfaction and resentment among employed professionals. There are two approaches in media reporting - the market approach and the approach of professional responsibility, and towards social services and the approach of blaming, especially towards professionals in the centers for social work. The theory of media representation was applied as the main theory for the interpretation of media representation. The aim of this research is to examine professional workers employed in social work centers in the Republic of Serbia on how they interpret the stereotypical image that the media create about them, as well as how they assess the quality of reporting by certain domestic media on their work. 242 professional workers from 49 centers for social work in the Republic of Serbia were examined. A survey was used as a data collection technique, where a questionnaire with a scale of Likert-type attitudes was used as an instrument. Factor analysis and descriptive statistical processing were used for data processing. Based on the obtained results, we conclude that professionals believe that the stereotypical image of them in the media is extremely negative, because they recognize that they are presented only with negative characteristics. In relation to the offered media, the respondents indicated that their work was poorly reported in those domestic media. It is important to know what the professionals of the centers for social work think about this topic, because the media have a great responsibility in forming attitudes and nurturing stereotypes about social work practitioners.
Keywords: media reporting, media image, social workers, center for social work, stereotypes